Spatial Formats under the Global Condition - Marung, Steffi (2019)
Contributions to this volume summarize and discuss the theoretical foundations of the Collaborative Research Centre at Leipzig University which address the relationship between processes of (re-)spatialization on the one hand and the establishment and characteristics of spatial formats on the other hand.